Comprehensive cholesterol screening: A preventive measure for heart disease at Pusaka Aji Kalibayem Healthy Heart Club - Mira Setiana; Bangkit Ina Ferawati (Universitas Muhammadiyah Magelang, 2024)
High cholesterol is a significant risk factor for cardiovascular disease often overlooked by the public. This community service aimed to increase public awareness among members of the Pusaka Aji Kalibayem Healthy Heart Club. By enhancing public knowledge about the importance of cholesterol checks, this initiative sought to prevent and early detect cardiovascular disease. The program encompassed health education, cholesterol screenings, and health consultations. A comprehensive cholesterol check program was conducted involving 35 members of the club. Results indicated a substantial increase in public awareness of cholesterol and its associated risks following participation. Before the program, only 25% of participants were aware of the need for regular cholesterol checks, which rose to 81% post-intervention. The comprehensive cholesterol check program at Pusaka Aji Kalibayem Healthy Heart Club effectively raised public awareness about cholesterol monitoring. Similar initiatives can be implemented in other communities to reduce cardiovascular disease risk through early detection and increased awareness.